2021
DOI: 10.1055/a-1336-3132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of physician-controlled guidewire manipulation during endoscopic ultrasound-guided hepaticogastrostomy (with video)

Abstract: Background and study aims Endoscopic ultrasound (EUS)-guided hepaticogastrostomy (HGS) may be most complex because of the EUS-guided biliary drainage procedure and variations in the course of the intrahepatic bile duct compared with the common bile duct (CBD). Appropriate guidewire insertion is essential. Physician-controlled guidewire manipulation (PCGW) might improve technical success rates of bile duct cannulation. The present study aimed to determine the technical feasibility and safety of PCGW during EUS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…EUS-CDS and HGS have the advantage of reducing the risk of tumor ingrowth and postprocedural pancreatitis since the stent does not cross the malignant stricture and the pancreatic duct orifice. Previous studies from high-volume centers reported a high technical and clinical success rate of CDS[111–121] and HGS [122–125,126 ▪ ,127 ▪ ] for distal MBO. Furthermore, CDS and HGS are reported as comparable in efficacy and safety [113,128–132].…”
Section: Endoscopic Approach For Malignant Biliary Obstructionmentioning
confidence: 91%
“…EUS-CDS and HGS have the advantage of reducing the risk of tumor ingrowth and postprocedural pancreatitis since the stent does not cross the malignant stricture and the pancreatic duct orifice. Previous studies from high-volume centers reported a high technical and clinical success rate of CDS[111–121] and HGS [122–125,126 ▪ ,127 ▪ ] for distal MBO. Furthermore, CDS and HGS are reported as comparable in efficacy and safety [113,128–132].…”
Section: Endoscopic Approach For Malignant Biliary Obstructionmentioning
confidence: 91%
“…However, guidewire manipulation in the liver impaction technique must be performed by an experienced assistant or controlled by the physician. 18 Finally, this study has several limitations, including its singlecenter design and retrospective nature. It is necessary to conduct a further prospective comparison study with another technique.…”
Section: Therapeutic Advances In Gastroenterologymentioning
confidence: 95%
“…Various techniques have been described to facilitate guidewire manipulation, such as the “liver impaction” technique to prevent wire shearing, 51 the “moving endoscope” technique to change the needle-scope angle, 52 the “jumping technique” of guidewire manipulation, 53 and the physician-controlled guidewire manipulation. 54 A few other factors, such as the minimum ductal diameter and optimum hepatic parenchyma length, have been systematically evaluated during the ductal puncture. A study of 174 HGS cases noted that a ductal diameter of ≤5 mm was associated with low technical success.…”
Section: Methodsmentioning
confidence: 99%